A Tale of Three Countries: Recovery after Banking Crises - Zsolt Darvas (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
Iceland, Ireland and Latvia experienced similar developments before the crisis, such as sharp increases in banks' balance sheets and the expansion of the construction sector. However the impact of the crisis was different: Latvia was hit harder than any other country in the world. Ireland also suffered heavily, while Iceland came out from the crisis with the smallest fall in employment, despite the greatest shock to the financial system. There were marked differences in policy mix: currency collapse in Iceland but not in Latvia, letting banks fail in Iceland but not in Ireland, and the introduction of strict capital controls only in Iceland. The speed of fiscal consolidation was fastest in Latvia and slowest in Ireland. Economic recovery has started in all three countries and there are several encouraging signals. The programme targets in terms of fiscal adjustment, structural reforms and financial reform are on track in all three countries. Iceland seems to have the right policy mix. Internal devaluation in Ireland and Latvia through wage cuts did not work, because privatesector wages hardly changed. The productivity increase was significant in Ireland and moderate in Latvia, yet was the result of a greater fall in employment than the fall in output, with harmful social consequences. The experience with the collapse of the gigantic Icelandic banking system suggests that letting banks fail when they had a faulty business model is the right choice. There is a strong case for a European banking federation.
Keywords: F31; F32; J30; O40; 330; banking crisis; banking sector restructuring; economic recovery; currency devaluation; internal devaluation; capital controls; fiscal adjustment; Bankenkrise; Bankenregulierung; Vergleich; Irland; Island; Lettland